TRPM2 Channel-Mediated ROS-Sensitive Ca2+ Signaling Mechanisms in Immune Cells - Syed Mortadza, Sharifah Alawieyah; Wang, Lu; Li, Dongliang; Jiang, Lin-Hua (Frontiers in Immunology, 2015)
Transient receptor potential melastatin 2 (TRPM2) proteins form Ca2+-permeable cationic channels that are potently activated by reactive oxygen species (ROS). ROS are produced during immune responses as signaling molecules as well as anti-microbial agents. ROS-sensitive TRPM2 channels are widely expressed in cells of the immune system and located on the cell surface as a Ca2+ influx pathway in macrophages, monocytes, neutrophils, lymphocytes, and microglia but preferentially within the lysosomal membranes as a Ca2+ release mechanism in dendritic cells; ROS activation of the TRPM2 channels, regardless of the subcellular location, results in an increase in the intracellular Ca2+ concentrations. Recent studies have revealed that TRPM2-mediated ROS-sensitive Ca2+ signaling mechanisms play a crucial role in a number of processes and functions in immune cells. This mini-review discusses the recent advances in revelation of the various roles the TRPM2 channels have in immune cell functions and the implications in inflammatory diseases.